Perspektywy badań demograficznych w Polsce - Borowski, Stanisław (Wydział Prawa i Administracji UAM, 1973)
Many of the demographic problems, stages and results of researches which are planned, are also identified in this paper with advisable development of population studies in Poland. The author divides all population problems requiring a resolution in the less or more mear future on: recognized and sítili not recognized with an additional division of the first ones on: retrospective, actual and prospective. As a horizon of his forecasting the author assumes the year 1990. Until the end of 1975 the development of population studies is already determined and up to that year the research plans being in force will be completed. Approximately in ten years covering the period of 1975 - 1985 already recognized problems will be solved. In the five-year plan of 1985 - 1990 the research workers will start to deal with the problems, which still are not recognized. The future retrospective problems can be defined in general as: population and the population reproduction in the period of industrialization and before the industrialization of Poland. The most important issue from the group of actual and prospective problems can be formulated as follows: optimization of structure and population processes in the age of techno-scientific revolution. The above mentioned issue has been divided into 17 topical groups and 76 subjects. As an example the following topical groups can be mentioned: evolution, factors and spatial differentiation of the population reproduction in Poland; demometric models; efficiency and risk of the antinatalistic methods and measures; the protection of motherhood; attitudes and family preferences of youth in maritial age; demographic forecasts; interdependence of population movement and socio-spatial population mobility; co-ordination of demographic, social and economic development as the task of population policy in the modern socialist state; an outline of theories concerning the demographic development in the age of techno-scientific revolution. In consequence the solution of that crucial problem connected with the new trends of demographic development will disclose round the year 1985 further questions referring to population diagnoses and forecasts for the end of the XX and the beginning of the XXI centuries as well as to the newest methodology of research and theory of demographic development. At the moment the scholars engaged into those studies are cooperating under the auspices of the Committee of Demographic Sciences, Polish Academy of Sciences. The Committee has following 6 sections: Paleodemography, Historical Demography, Social Demography, Medical Demography, Population Policy and Theory of Demography.
The Perspectives of Population Studies in Poland